Clinical aspects of the use of electrostimulation at vertebrogenic pathology of the lumbosacral spine department, literature review - Samosiinyi Андрій (Psychosomatic Medicine and General Practice, 2019)
This is a conference abstract from the Scientific-practical conference "Psychosomatic medicine: science and practice". It is dedicated to clinical aspects of the use of electrostimulation at vertebrogenic pathology of the lumbosacral spine department.